Atomic Absorption Spectrophotometry-Based Evaluation of Iron and Chromium in Community Water Sources - Apriani, Suci (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: To determine the presence of heavy metal content, especially iron (Fe) and chromium (Cr) in artesian water wells and residents in Rejo Sari Village.. Methodology: In determining pH, pH meter and universal indicator paper were used. The pH values ​​obtained were 6.5; 6.4; 5.9; 7.4; 6.5 and 7.5. Determination of iron (Fe) and chromium (Cr) content was carried out using the Atomic Absorption Spectrophotometry (AAS) method. Main Findings: The results of the study showed that the concentrations of iron (Fe) were 1.9615 ppm, 0.4692 ppm, 0.4692 ppm, 0.4461 ppm, 1.5615 ppm, and 0.2769 ppm, respectively. One sample with chromium (Cr) concentration was detected at 0.06 ppm. Novelty/Originality of this study: This study presents a novel contribution by comparing the heavy metals Fe and Cr content in two types of well water sources—artesian wells and ring wells—specifically in a densely populated residential area, using an AAS-based quantitative analysis approach rarely applied simultaneously to both metals in a local context. This study also emphasizes the significance of spatial and environmental quality on heavy metal contamination, which has not been widely addressed in similar studies in the region.